(untitled) (The International Journal for Scientific Research, 2024)
The study evaluated the effect of hypothyroidism on experimental rats (Rattus norvegicus). All animals were housed, breeding and adapted, and then only (50) virgin females were chosen. The animals subdivided into two groups, the first group was regarded as control, while the second group were treated with propylthiouracil (ptu) as a drug with a dose (0.05%) to induce hypothyroidism, then the females left mating and studied the changes after (14.5,16.5,18.5,20.5and 21.5) days post gestation. In this study, the results of ultra-structural changes in the thyroid gland from maternal rats and fetus with induced hypothyroidism and their fetus at each period of gestation were clarified with transmission electron microscopy; these changes included alteration in apical surface and cytoplasm of follicular cells that lining the thyroid follicles by Changes in shapes of microvilli. Like blebs and protrusions, also dilated rough endoplasmic reticulum, increased with lysosomes, and the empty vacuoles appeared more than the dense vesicles. In addition to that, there was an increase in mitochondria and golgi apparatus cisternae, the nucleus of follicular cell showed changes in their chromatin and irregular outlines and more cellular debris. Also, the pictures referred to the deposition of crystals from iodine salts in most follicular cells and the connective tissue showed thickening that separated thyroid follicles from rat fetus with induced hypothyroidism at (18.5) days post gestation. Biochemical results revealed to a significant increase in the mean concentration of (TSH)in all pregnant rats with hypothyroidism compared with control females, also there were a decreased in both (T3 and T4) hormones in the serum of pregnant rats in the hypothyroidism group compared to the control group, during each period of gestation (14.5,16.5,18.5,20.5 and 21.5) days. Levels of some oxidative enzymes (GSH and MDA) were also determined in this study; there was a significant increase in their concentration in serum of pregnant rats related to the hypothyroidism group compared with their concentration in the control group.